2012
DOI: 10.3144/expresspolymlett.2012.70
|View full text |Cite
|
Sign up to set email alerts
|

Response surface analysis of structural, mechanical, and permeability properties of polyethylene/Na+-montmorillonite composites, prepared by slurry-fed melt intercalation

Abstract: Abstract. Samples were produced by injecting Na + -montmorillonite (Na + -MMT) slurry into a co-rotating twin-screw extruder. Na + -MMT was modified inside the extruder, in an in-situ process, and blended with the LDPE/LLDPE in melt state. Three different types of alkyl ammonium salt (ALAMS) were used as modifier to study the effect of chemical composition and chain length of ALAMS on the dispersion of nanoparticles. Also, the effect of nanoclay content on structural, mechanical, and permeability properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 41 publications
(54 reference statements)
1
33
0
Order By: Relevance
“…Specific mass ranged from 2.19 g cm -3 to 2.59 g cm -3 for MtNa + and NZ-Ch respectively. These values are also in accordance with those reported for montmorillonite (2.50-2.76 g cm -3 ) 12,19) and zeolites (2.36-2.39 g cm -3 ) 11,12) .…”
Section: Physicohemical Characteristics Of the Aluminosilicatessupporting
confidence: 82%
“…Specific mass ranged from 2.19 g cm -3 to 2.59 g cm -3 for MtNa + and NZ-Ch respectively. These values are also in accordance with those reported for montmorillonite (2.50-2.76 g cm -3 ) 12,19) and zeolites (2.36-2.39 g cm -3 ) 11,12) .…”
Section: Physicohemical Characteristics Of the Aluminosilicatessupporting
confidence: 82%
“…(1) A chemical reaction occurs between the active functional groups of the compatibilizer and the functional groups of the plant fiber [42], and this reaction forms either a chemical bond or a hydrogen bond, both of which commonly occur when polyethylene-based compatibilizer reacts with the hydroxyl groups [23] of the fiber or when the anhydride of MAPE [43,44,45] reacts with the glycosidic bond [46] (esterification)of the wood fiber; (2) This bonding reduces the polarity and hydrophilic nature of the plant fiber and improves the bonding strength between the wood fibers and the non-polar matrix, in accordance with the principle of compatibility between similar polarities; (3) The long chain within the compatibilizer (MAPE) can be inserted into the matrix, thereby enhancing the combination of the compatibilizer with the matrix as the molecular chain intertwines within the region of insertion [16,29,45]. Thus, the compatibilizer can effectively improve the interfacial bonding character of the composite by combining these three functions [30,47]. The findings of similar, previously reported experiments do not need to be repeated here, and the mechanisms by which the composite microstructure that has been integrated into one material and has become soft and dense upon the addition of MAPE are self-evident.…”
Section: Resultsmentioning
confidence: 99%
“…Water-assisted method is recently introduced [19][20][21] to acquire PE=clay nanocomposites with augmented barrier and mechanical properties. Several studies have shown that [19][20][21][22] employing a ternary ammonium salt solution other than pure water [18] enhances the permeability resistance and impact strength of PE=Nanoclay systems through improved intercalation. However, the main drawback of this method is concerned with high viscosity of salt solution which causes process difficulties.…”
Section: Introductionmentioning
confidence: 99%